On some common fixed point results for two infinite families of uniformly L-Lipschitzian total asymptotically quasi-nonexpansive mappings - Nuntadilok, Buraskorn; Kingkam, Pitchaya; Nantadilok, Jamnian; Samanmit, Khanitin (Fixed point theory and algorithms for sciences and engineering, 2024)
In this manuscript, we introduce a new class of uniformly L -Lipschitzian and total asymptotically quasi-nonexpansive mappings, which is significantly more general than many known nonexpansive mappings that appeared before. We establish some convergence and Δ-convergence theorems for two infinite families of such mappings in the setting of CAT( κ ) spaces. Our results refine, generalize, and improve several corresponding results in the existing literature.